Free-standing sulfonated graphene-polypyrrole-polyethylene glycol foam for highly flexible supercapacitors. (22nd August 2022) - Fu, Jialong; Cai, Chaoyue; Zhang, Zhiheng; Wang, Xiaoying; Wang, Cheng; Tu, Haoyu; Wu, Han; Zhao, Yibo; Zhang, Chengyan; Zhu, Jing; Zhao, Xinhui; Xu, Ruibo; et al.
Abstract: Flexible and free-standing sulfonated graphene-polypyrrole-polyethylene glycol (SGE-PPy-PEG) foam electrodes were prepared via one-step electrodeposition process, exploiting coupling between negatively charged sulfate groups and positively charged pyrrole rings, followed with the sacrifice step of inner Ni foam structure. The resulted SGE-PPy-PEG foam electrodes were fully characterized before they were assembled into wearable supercapacitors. A typical foam electrode shows a significant specific capacitance of 528 Fg -1 aligned with excellent electrochemical durability (93% capacitance retention after 8000 charge-discharge cycles) in a standard three electrode system. When assembled as a single symmetric supercapacitor device (SSC), it also exhibits remarkable specific capacitance (per area/per volume) of 212.4 mFcm −2 /1416 mFcm −3 and retains 94% capacitance after 4000 cycles. Furthermore, there is no observed negligible capacitance loss under various bending degrees up to ±180 °C, a demo of extraordinary mechanical flexibility. A rolled-up device, made from a long strip of SGE-PPy-PEG foam electrode, is able to power a red light-emitting diode light for more than 1 min after fully charged. Moreover, three SCs connected in series as a wrist band can successfully light up six colorful LED, demonstrating the great potential of flexible SGE-PPy-PEG foam in real wearable applications. Graphical abstract: Image 1 Highlights: Flexible & free-standing foam electrodes were prepared via electrodeposition process. The foam electrode shows a large specific capacitance with excellent durability. An all solid state device was fabricated showing exceptional flexibility. Three SCs connected in series as a wrist band can light up six colorful LED.